HOW FAR CAN GET FRB PROGENITOR NEUTRON STARS FROM THEIR BIRTHPLACE? - Otebay, A.; Kalambay, M.; Shukirgaliyev, B. (Recent Contributions to Physics, 2021)
The recent studies show evidence of magnetars – young neutron stars being good candidates of fast radio birth sources. Neutron stars can form as remnants of type II supernovae explosions of young stars. That is, such young neutron stars should be associated with their parent young star cluster. We study how these FRB source candidates can get far out of their birthplace if they escape clusters due to their high kick velocity. Therefore, we perform numerical simulations of the early evolution of star clusters and trace all young neutron stars. We found that neutron stars can remain in clusters, as well as escape them during their possible magnetar phases. There is no preference in time during the cluster evolution for FRBs to happen in or out of the parent cluster. The maximum distance the candidate FRB progenitors could escape from the cluster does not exceed 250 pc. That is, the high dispersion measure of FRBs might be influenced by the expulsed ionized residual star-forming gas in the parent molecular cloud.